THE EFFECTIVENESS OF THE DUAL EDUCATION SYSTEM (American Journal of Pedagogical and Educational Research, 2024)
New pedagogical technologies used in the educational process serve to develop skills and competencies necessary for life. The effectiveness of the dual education system is being confirmed. In fact, education should be an integral part of real life, teaching processes should prepare the learner for all aspects of life and professional activity. Each academic subject serves to form one common competence. A person learns and assimilates existence through the sense organs, but understanding related to perception is not studied separately as a skill and qualification, nor does it exist as a competence in the system of training a well-rounded person in didactics. After all, a person goes through the processes of viewing and understanding before reading and understanding in the course of listening. In the article, reading comprehension is researched as an important pedagogical factor, not a simple physiological phenomenon, and its description is given at the level of skill, skill and competence. It is based on the fact that observation is a necessary tool for forming analytical thinking.